Felt or thought: distinct mechanisms underlying exploitative leadership and abusive supervision - Pircher Verdorfer, Armin (Journal of business ethics, 2024)
The last two decades have seen a mounting fascination with unethical and destructive forms of leadership. Yet, do we know what all encapsulates this "dark" side of leadership? Despite initial evidence that exploitation is a notable addition to the unethical leadership scene, our understanding of its distinctiveness as well as of how and why it exerts its negative effects is limited. We speak to this gap by testing the distinct mechanisms through which exploitative leadership - relative to the more popular counterpart, abusive supervision - affects followers. Borrowing from the aggression literature, we describe exploitative leadership and abusive supervision as varying forms of aggression that undermine followers' satisfaction with the leader via altered experiences of their social exchange relationship. Our theoretical model proposes that abusive supervision, as an inherently interpersonal provocation, primarily implicates followers' emotional experiences within the social exchange process. By contrast, given its inherent focus on self-interest, exploitative leadership is assumed to affect followers primarily through the cognitive understanding of the social exchange. Results from multiple studies using different samples, measures, and research designs provide general support for our predictions. In sum, the evidence emerging from our data shows that exploitative leadership is not a symptom of construct proliferation but rather, adds cumulative knowledge to the field of unethical and destructive leadership.